Left atrial appendage aneurysm. (26th November 2019) - Jiang, Bo; Wang, Xi; Liu, Feng; Song, Long
Abstract: Left atrial appendage aneurysm is an infrequent abnormality presenting as atrial tachyarrhythmias, progressive dyspnoea, atypical chest pain and systemic thromboembolism. Surgical excision is considered to prevent fatal complications, even in asymptomatic cases. We describe the case of a 44-year-old woman with a history of acute cerebral infarction caused by emboli from a giant left atrial appendage aneurysm, which is the largest one reported to date. Histopathology and Masson staining confirmed the final diagnosis.